Effect of short-term exposure to high temperatures on the reproductive behavior and physiological enzyme activities in the fruit fly Zeugodacus tau (Walker) - Li, Mao; Wei, Xiao-Man; Li, Juan; Wei, Shi-Ming; Zhang, Jin-Long; Chen, Guo-Hua; Zhang, Xiao-Ming (Frontiers in Physiology, 2023)
Zeugodacus tau is an economically important invasive pest of various vegetables and fruits. In this study, we evaluated the effects of short-term (12 h) exposure to high temperatures on the reproductive behaviors and physiological enzyme activities of adult Z. tau flies. When compared to the control group, the mating rate in the treated group increased significantly after exposure to 34°C and 38°C. After 34°C exposure, the mating rate of the control♀-treated♂ mating was the highest (60.0%). The use of high temperatures for a short period reduced the pre-mating period and lengthened the duration of copulation. After 38°C exposure, the mating between treated♀ and treated♂ had the shortest pre-mating period of 39.0 min and the longest copulation duration of 67.8 min. Mating after a brief exposure to high temperatures had a negative impact on female reproduction, whereas mating with males who previously had a brief exposure to 34°C and 38°C significantly increased female fecundity. After 40 °C exposure, the mating between treated♀ and control♂ showed the lowest fecundity and hatching rate of 293.25 eggs and 25.71%, respectively. The mating between control♀ and treated♂ showed the highest fecundity of 1,016.75 eggs after exposure to 38°C. The SOD, POD, and CAT activities exhibited significant changes (increase or decrease) after the short-term exposure of Z. tau adults to high temperatures. After being exposed to 38°C, SOD activity increased by 2.64 and 2.10 times in females and males in the treated group, respectively, compared to the SOD activity in the control group. The AchE, CarE, and GST activities first increased and then decreased with the increase in temperature. CarE activity changed the most after exposure to 38°C, with females and males in the treated group increasing by 7.81 and 1.69 times, respectively, compared to the activity in the control group. In conclusion, mating strategy and physiological stress are important adaptive mechanisms of Z. tau for adapting to short-term heat stress in a sex-specific manner.